Implementasi Penilaian Autentik Kurikulum 2013 di Madrasah Tsanawiah (MTs) Al-Khoiriah Cikulur-Lebak, Banten - Mumu Zainal Mutaqin (LPPM STAI La Tansa Mashiro, 2016)
Assessment is a generic term that includes all the methods used to assess a student's abilities, the 2013 Curriculum is the standard setting of the assessment. The purpose of this study is for The purpose of this study is as follows: 1) To know the basic concept of assessment of the 2013 curriculum in MTs Al Khoiriyyah; 2) To know Implementation of 2013 curriculum assessment in MTs Al Khoiriyyah 3) To know the implication of 2013 curriculum assessment in MTs Al Khoiriyyah with research method using qualitative approach. This research is used to understand about the phenomenon that occurred in MTs Al Khoiriyyah Cikulur about the implementation of assessment of curriculum 2013. This type of research used qualitative descriptive research, the results of this study The concept of appraisal applied in MTs Al Khoiriyyah Cikulur derived from Kemenag submitted to the Regional Office (Kanwil) then to Madrasah Education of Lebak Regency, by Madrasah Education the concept is submitted to Madrasahs in all accredited Lebak District applying the 2013 curriculum. The 2013 Curriculum Assessment Implementation is divided into the assessment of affective aspects, cognitive aspects and psychomotor aspects. Affective or attitudinal assessment that includes Core Competencies and Core Competencies in which teachers make observations, peer assessments, self-ratings, and personal journals. Cognitive Assessment (Core Competence-3) Teachers judge from the results of students working on problems on the Print Book, LKS or questions from the teacher. Psychomotor Assessment (Core Competence-4) is a teacher assessing the results of students making projects or portfolios, performance (performance), memorization and practice. The 2013 Curriculum Assessment at MTs Al Khoiriyyah Cikulur has implications for changes in students' behavior, attitude, knowledge and skills. Students are assessed thoroughly and objectively according to the student's condition. Assessment on aspects of attitude affect the change in student attitudes become more disciplined, more orderly, and become more obedient to teachers and the rules of Madrasah. Thus, the learning outcomes of the cognitive and psychomotor aspects become balanced.Penilaian adalah istilah umum yang mencakup semua metode yang digunakan untuk menilai kemampuan peserta didik, Kurikulum 2013 adalah penataan standar penilaian. Tujuan dalam penelitian ini adalah untuk Adapun tujuan pembahasan penelitian ini adalah sebagai berikut: Untuk mengetahui Implikasi penilaian kurikulum 2013 di MTs Al Khoiriyyah dengan metode penelitian menggunakan pendekatan kualitatif. Penelitian ini digunakan untuk memahami tentang fenomena yang terjadi di MTS Al Khoiriyyah Cikulur tentang implementasi penilaian kurikulum 2013. Jenis penelitian yang digunakan ini termasuk penelitian deskriptif kualitatif, hasil dalm penelitian ini Konsep penilaian yang diterapkan di MTS Al Khoiriyyah Cikulur berasal dari Kemenag disampaikan ke Kantor Wilayah (Kanwil) kemudian ke Pendidikan Madrasah Kabupaten Lebak, oleh Pendidikan Madrasah konsep tersebut disampaikan ke Madrasah-Madrasah di seluruh Kabupaten Lebak yang terakreditasi yang menerapkan kurikulum 2013. Implementasi Penilaian Kurikulum 2013 dibagi menjadi penilaian aspek afektif, aspek kognitif dan aspek psikomotor. Penilaian afektif atau sikap yang meliputi Kompetensi Inti-1 dan Kompetensi Inti-2 yang mana guru melakukan observasi, penilaian antar teman, penilaian diri, dan jurnal pribadi.